Naucleopsis tubulata (Moraceae), a new overlooked species from the Brazilian Amazon, and the re-establishment of Naucleopsis insculptula - Dos Santos, Alessandra; Gaglioti, André Luiz; Pederneiras, Leandro Cardoso; Romaniuc-Neto, Sergio (Phytotaxa, 2019)
Naucleopsis tubulata (Moraceae), a new species endemic to the Brazilian Amazon is described and illustrated in this paper. The conical to tubular shape of the perianth of the pistillate flower and fruit, the narrowly oblong shape of the leaves, and the filaments connate at the base differ from other species in the genus. This new species shows morphological similarities with N. caloneura and N. insculptula. The latter, previously treated as a synonym of N. caloneura, is re-established in this paper. We here present a taxonomic treatment for the new species of Naucleopsis, reestablished N. insculptula, and an updated identification key for the Naucleopsis species that occur in the Boreal Brazilian Domain.